STATUS GIZI BERPENGARUH TERHADAP KEJADIAN PNEUMONIA PADA BALITA DI RSUD dr. M YUNUS BENGKULU TAHUN 2017 - Wahyuni, Elly; Yorita, Epti; Anissa, Kintan (Politeknik Kesehatan Kemenkes Bengkulu, 2019)
Abstract: Disease Pneumonia is an acute respiratory infection that attacks lung tissue, characterized by a cough accompanied by rapid breath or shortness of breath. Riskesdas in 2013 shows the incidence of pneumonia in Indonesia is 1.8% with a prevalence of 4.5%. If translated by number then at least from 23 infants who died every hour and 4 of them because of pneumonia and in 2015 there are 554,650 cases of reported pneumonia. This study aims to determine the relationship of nutritional status with the incidence of pneumonia in infants in hospitals dr. M Yunus Bengkulu Year 2017. The research method used is a quantitative survey with case control approach retrospectively. The number of samples for the case was 28 toddlers and for the control sample of 56 infants. The results of this study found that the variables of nutritional status and age there is a significant relationship with the incidence of pneumonia in toddlers with the value p = 0.00 OR = 9.2273 and p = 0.001 OR = 1.077. And there is no sex relationship with the incidence of pneumonia with p = 1.00. So the conclusion of this study is there is a significant relationship between nutritional status and age with the incidence of pneumonia in infants in hospitals dr. M Yunus Bengkulu where the variable age as an outside variable. The suggestion of this research is can be used as literature to increase the insight and information and health education, can increase the knowledge of health personnel to be more competent in handling the case of pneumonia, and hopefully the result of this research can be used as input or comparison material for subsequent researchers and Other researchers may develop research by linking other factors.